2014
DOI: 10.1371/journal.pone.0110507
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Expression of the AtDREB1A Gene in Transgenic Peanut-Conferred Tolerance to Drought and Salinity Stresses

Abstract: Research on genetic transformation in various crop plants using the DREB1A transcription factor has shown better abiotic stress tolerance in transgenic crops. The AtDREB1A transgenic peanut (Arachis hypogaea L. cv. GG 20), which was previously developed, was characterized in terms of its physio-biochemical, molecular and growth parameters. The tolerance of this transgenic peanut to drought and salinity stresses was evaluated at the seedling (18 days old) and maturity stages. Transgenic peanut lines showed impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 68 publications
11
51
0
Order By: Relevance
“…fastigiata (Krapovickas and Rigoni, 1960). It is cultivated in more than 100 countries, mostly by the small and marginal farmers, under low-input conditions (Bhauso et al, 2014; Sarkar et al, 2014). Peanut is one among the major oilseed crops, which contribute to the bulk of total oil production worldwide (Mishra et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…fastigiata (Krapovickas and Rigoni, 1960). It is cultivated in more than 100 countries, mostly by the small and marginal farmers, under low-input conditions (Bhauso et al, 2014; Sarkar et al, 2014). Peanut is one among the major oilseed crops, which contribute to the bulk of total oil production worldwide (Mishra et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It could be due to the positive regulation of rd29A promoter which involved in stress inducible expression of transgene. Similarly, higher expression of AtDREB1A was seen in groundnut transgenic plants which were regulated by rd29A promoter (Sarkar et al, 2014, 2016). It indicated that there was positive correlation between regulation of transgene and stress tolerance.…”
Section: Discussionmentioning
confidence: 91%
“…The genes from Salicornia brachiata, ascorbate peroxidase ( SbAPX ), and abscisic acid stress ripening ( SbASR ) genes when expressed in groundnut displayed salt and drought stress tolerance coupled with more chlorophyll retention and enhanced levels of relative water content under normal/stress conditions (Singh et al, 2014; Tiwari et al, 2015). The transcription factors from Arabidopsis, AtNAC2 (Patil et al, 2014), AtDREB1A (Sarkar et al, 2014, 2016) and horsegram, MuNAC4 (Pandurangaiah et al, 2014) were exhibited drought and salt stress tolerance in groundnut by reducing the membrane damage and improving scavenging of reactive oxygen species scavenging (ROS). Groundnut transgenic plants ( cv TMV-2) simultaneously expressing three TFs ( AtDREB2A, AtHB7 , and AtABF3 ) displayed to increase drought, salinity, and oxidative stress tolerance compared to wild type (Pruthvi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…India, peanut is mostly grown under rain-fed conditions, mostly by resource-poor farmers, and, hence, is most likely encountered by abiotic stresses like drought and salinity (Sarkar et al 2014;Bhauso et al 2014a, b).…”
Section: Introductionmentioning
confidence: 99%